Fabrication of Gastro-Floating Famotidine Tablets: Hydroxypropyl Methylcellulose-Based Semisolid Extrusion 3D Printing - Hyun Seok Yang; Dong Wuk Kim (MDPI AG, 2023)
Semisolid extrusion (SSE) three-dimensional (3D) printing uses drug-loaded paste for the printing process, which is capable of constructing intricate 3D structures. This research presents a unique method for fabricating gastro-floating tablets (GFT) using SSE. Paste-loaded famotidine with a matrix made of hydroxypropyl methylcellulose (HPMC) were prepared. Nine 3D printed tablets were developed with different HPMC concentrations and infill percentages and evaluated to determine their physicochemical properties, content uniformity, dissolution, and floating duration. The crystallinity of the drug remained unchanged throughout the process. Dissolution profiles demonstrated the correlation between the HPMC concentration/infill percentage and drug release behavior over 10 h. All the fabricated GFTs could float for 10 h and the Korsmeyer-Peppas model described the dissolution kinetics as combination of non-Fickian or anomalous transport mechanisms. The results of this study provided insight into the predictability of SSE 3D printability, which uses hydro-alcoholic gel-API blend materials for GFTs by controlling traditional pharmaceutical excipients and infill percentages. SSE 3D printing could be an effective blueprint for producing controlled-release GFTs, with the additional benefits of simplicity and versatility over conventional methods.